2019
DOI: 10.13057/biodiv/d200303
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of the selected Cucumis L. species and accessions using leaf architecture characters

Abstract: Abstract. Masungsong LA, Belarmino MM, Buot IEJr. 2019. Delineation of the selected Cucumis L. species and accessions using leaf architecture characters. Biodiversitas 20: 629-635. Regardless of the several attempts of the early and recent studies to separate the wild species of Cucumis from the cultivated ones, there is still taxonomic confusion brought about by the similarities in morphology of the genus. In a gene bank with so many species and accessions of Cucumis stored, it is appropriate to delineate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…The taxonomist's attention to the leaves' size comparison begins with the theory stating the shapes are not affected by the environment (Balduzzi et al 2017) and the venation is derived genetically (Dickinson et al 1987;Mishra et al 2010). Due to the availability and variations, the leaf is organ-rich information and the source of taxonomy data (Kareem et al 2018;Masungsong et al 2019). Leaf venation is also used to delineate between two confusing Dipterocarpaceae species in the same genera (Mazo and Aribal 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The taxonomist's attention to the leaves' size comparison begins with the theory stating the shapes are not affected by the environment (Balduzzi et al 2017) and the venation is derived genetically (Dickinson et al 1987;Mishra et al 2010). Due to the availability and variations, the leaf is organ-rich information and the source of taxonomy data (Kareem et al 2018;Masungsong et al 2019). Leaf venation is also used to delineate between two confusing Dipterocarpaceae species in the same genera (Mazo and Aribal 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, these structures can be challenging to investigate due to their seasonality (da Silva et al 2015). The use of plant vegetative charac-ters such as the leaves are similarly important since they are present throughout the plant's life span Masungsong et al 2019a). Leaf architecture is one of the most valuable tools that is being utilized in many recent taxonomic studies .…”
Section: Introductionmentioning
confidence: 99%
“…Cucumis sativus and C. melo are just two of the many economically important members of the genus. Several leaf architectural studies on Cucumis have been conducted and contributed to the identification, classification, and delineation of the genus (Rao and Rao 2015;Masungsong et al 2019a;Masungsong et al 2019b;Averion-Masungsong and Buot 2020;Masungsong et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Roth-Nebelsick (2001) has found that in general, the leaf venation pattern of a species is genetically fixed, providing the basis for using the leaf venation as a taxonomic tool. Some applications include Laraño and Buot (2010) on Malvaceae, and Masungsong et al in 2019 on Cucumis species, among others. A comprehensive review of the utility of leaf architecture for resolving plant taxa controversies was published by Buot (2020).…”
Section: Introductionmentioning
confidence: 99%